Modified polytetrafluoroethylene, molded article, and method for producing stretched porous body
By increasing the amount of PFBE added to the modified polytetrafluoroethylene and adjusting its thermal instability index and area ratio S, the problem of insufficient fracture strength of tensile porous bodies in the prior art is solved, and a significant increase in fracture strength is achieved.
Patent Information
- Application Number
- CN202380054758.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-19
- Filing Date
- 2023-07-14
- Publication Date
- 2025-03-07
AI Technical Summary
The fracture strength of the tensile porous bodies obtained by the existing modified polytetrafluoroethylene has not yet reached the optimal level.
By increasing the amount of PFBE added to the modified polytetrafluoroethylene, the thermal instability index and area ratio S are adjusted, so that the thermal instability index is 0 to 15, and the area ratio S is below 0.70, thereby improving the fracture strength of the tensile porous body.
The tensile porous body with excellent fracture strength is achieved, and the performance of modified polytetrafluoroethylene is improved.
Smart Images

Figure CN119585325A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing modified polytetrafluoroethylene, a formed article and a stretched porous body. Background Art
[0002] Polytetrafluoroethylene is used in a variety of applications due to its excellent properties. Among them, various studies have been conducted on modified polytetrafluoroethylene obtained by polymerizing tetrafluoroethylene and perfluoroalkylethylene (Patent Documents 1 and 2). Prior art literature Patent Literature
[0003] Patent Document 1: International Publication No. 2017 / 030094 Patent Document 2: Japanese Patent No. 4031433 Summary of the invention Technical problem to be solved by the invention
[0004] In recent years, there has been a demand for further improvement in the performance of modified polytetrafluoroethylene. The present inventors have studied stretched porous bodies obtained by using modified polytetrafluoroethylene described in Patent Documents 1 and 2, and have found that there is still room for improvement in terms of breaking strength.
[0005] An object of the present invention is to provide a modified polytetrafluoroethylene capable of producing a stretched porous body having excellent breaking strength. Another object of the present invention is to provide a method for producing a formed article and a stretched porous body. Technical solutions adopted to solve technical problems
[0006] In order to achieve the above object, the present inventors have conducted in-depth research and found that the above object can be achieved through the following technical solutions.
[0007] That is, the present inventors have discovered that the above-mentioned problem can be solved by the following technical solution. [1] A modified polytetrafluoroethylene, The modified polytetrafluoroethylene comprises units based on tetrafluoroethylene and units based on the following other monomers copolymerizable with tetrafluoroethylene, wherein: The thermal instability index is 0 to 15. The area ratio S calculated by the following method is less than 0.70; Other monomers: At least one selected from perfluoro(alkyl vinyl ether), hexafluoropropylene, and fluoroalkylethylene; Calculation method of area ratio S: The modified polytetrafluoroethylene which has not been heated to a temperature of 300° C. or higher is measured by a differential scanning calorimeter at a heating rate of 1° C. / min, and the obtained differential calorimetric curve is secondarily differentiated to obtain a second differential curve. In the quadratic differential curve, there is a minimum value Mi1 in the range of 19 to 21°C. A point L21 showing a maximum value on the lowest temperature side among the maximum values on the higher temperature side than the temperature showing the minimum value Mi1 and a point L22 showing a maximum value on the highest temperature side among the maximum values on the lower temperature side than the temperature showing the minimum value Mi1 are connected into a straight line, and an area S1 of a region enclosed by this straight line and the quadratic differential curve is calculated. In the quadratic differential curve, there is a minimum value Mi2 in the range of 15 to 17°C. A point L23 showing a maximum value on the lowest temperature side among the maximum values on the higher temperature side than the temperature showing the minimum value Mi2 and a point L24 showing a maximum value on the highest temperature side among the maximum values on the lower temperature side than the temperature showing the minimum value Mi2 are connected into a straight line, and an area S2 of a region enclosed by this straight line and the quadratic differential curve is calculated. The area ratio S is calculated as the ratio of the area S1 to the area S2. [2] The modified polytetrafluoroethylene according to [1] above, wherein the other monomer is a fluoroalkylethylene. [3] The modified polytetrafluoroethylene according to [1] above, wherein the other monomer is CH 2 =CH(CF 2 ) 4 F. [4] The modified polytetrafluoroethylene according to any one of [1] to [3] above, wherein the standard specific gravity of the modified polytetrafluoroethylene is 2.130 to 2.160. [5] The modified polytetrafluoroethylene according to [1] or [2], wherein the content of the units based on the other monomer in the modified polytetrafluoroethylene is 1000 to 6000 ppm by mass relative to the content of the units based on all monomers in the modified polytetrafluoroethylene. [6] The modified polytetrafluoroethylene according to [3], wherein the modified polytetrafluoroethylene is based on the CH 2 =CH(CF 2 ) 4 The content ratio of the F unit is 1500 to 6000 mass ppm based on the content of the units based on all monomers in the modified polytetrafluoroethylene. [7] The modified polytetrafluoroethylene according to any one of [1] to [6] above, which is used for paste extrusion molding. [8] A molded product obtained by extrusion molding the modified polytetrafluoroethylene paste according to any one of [1] to [7] above. [9] A method for producing a stretched porous body, comprising extruding the modified polytetrafluoroethylene paste described in any one of [1] to [7] to obtain extruded beads, and stretching the extruded beads to obtain a stretched porous body. Effects of the Invention
[0008] The present invention can provide a modified polytetrafluoroethylene capable of producing a stretched porous body having excellent breaking strength. Furthermore, the present invention can also provide a method for producing a molded product and a stretched porous body using the modified polytetrafluoroethylene. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 An example of a differential calorimetry curve measured using the modified polytetrafluoroethylene of the present invention is shown. Figure 2 An example of a second-order differential curve obtained by secondarily differentiating a differential calorimetric curve measured using the modified polytetrafluoroethylene of the present invention is shown. DETAILED DESCRIPTION
[0010] The meanings of the terms in the present invention are as follows. "Unit" refers to the general term for the atomic group derived from one monomer molecule directly formed by the polymerization of monomers. The content (mass %) of each unit relative to all units contained in the polymer can be obtained by analyzing the polymer by solid nuclear magnetic resonance (NMR) method, or it can be inferred from the feed amount of each monomer. Usually, the content of each unit calculated from the feed amount of each monomer is roughly the same as the actual content of each unit. The "~" indicating a numerical range indicates a range including the numerical values recorded before and after it as the lower limit and the upper limit. In the numerical ranges recorded in the classification in this specification, the upper limit or lower limit recorded in a certain numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other classifications. In addition, in the numerical ranges recorded in this specification, the upper limit or lower limit recorded in a certain numerical range can also be replaced by the values shown in the embodiments. In the present specification, a combination of two or more preferred aspects is a more preferred aspect.
[0011] As a characteristic point of the modified polytetrafluoroethylene (hereinafter also referred to as "modified PTFE") of the present invention, it includes units based on tetrafluoroethylene (hereinafter also referred to as "TFE") (hereinafter also referred to as "TFE units") and units based on other monomers, a thermal instability index of 0 to 15, and an area ratio S calculated by the method described later of not more than 0.70.
[0012] <Modified PTFE> The modified PTFE of the present invention comprises TFE units and units based on other monomers.
[0013] (TFE unit) The modified PTFE generally contains a polymer having TFE units as a main component. The main component means that the content of the polymer having TFE units is 99.000% by mass or more, preferably 99.400% by mass or more, based on the modified PTFE.
[0014] (Units based on other monomers) The other monomer is at least one selected from perfluoro(alkyl vinyl ether) (hereinafter also referred to as "PAVE"), hexafluoropropylene (hereinafter also referred to as "HFP"), and fluoroalkylethylene (hereinafter also referred to as "FAE"). As the other monomer, FAE is preferred.
[0015] As PAVE, CF 2 =CFOCF 3 (hereinafter also referred to as "PMVE"), CF 2 =CFOCF 2 CF 3 CF 2 =CFOCF 2 CF 2 CF 3 (hereinafter also referred to as "PPVE"), CF 2 =CFOCF 2 CF 2 CF 2 CF 3 CF 2 =CFO(CF 2 ) 8 F. Among them, PMVE or PPVE is preferred. As FAE, CH 2 =CH(CF 2 ) 2 F, CH 2 =CH(CF 2 ) 3 F, CH 2 =CH(CF 2 ) 4 F, CH 2 =CF(CF 2 ) 3 H, CH 2 =CF(CF 2 ) 4 H. Among them, CH 2 =CH(CF 2 ) 4F or CH 2 =CH(CF 2 ) 2 F, preferably CH 2 =CH(CF 2 ) 4 F (hereinafter also referred to as "PFBE").
[0016] The content ratio of units based on other monomers in the modified PTFE is preferably 1000 mass ppm or more, more preferably 1500 mass ppm or more, further preferably 1700 mass ppm or more, particularly preferably 2000 mass ppm or more, relative to the content of units based on all monomers in the modified PTFE. From the viewpoint of better heat resistance of the modified PTFE, the content ratio of units based on other monomers in the modified PTFE is preferably 6000 mass ppm or less, more preferably 5500 mass ppm or less, and further preferably 5000 mass ppm or less relative to the content of units based on all monomers in the modified PTFE. Hereinafter, an example in which PFBE is used as another monomer will be described.
[0017] (PFBE unit) From the perspective of achieving better breaking strength of the stretched porous body, the content ratio of the PFBE unit in the modified PTFE is preferably 1000 mass ppm or more, more preferably 1500 mass ppm or more, further preferably 1700 mass ppm or more, and particularly preferably 2000 mass ppm or more, relative to the content of the units based on all monomers in the modified PTFE. From the viewpoint of better heat resistance of the modified PTFE, the content ratio of the PFBE unit in the modified PTFE is preferably 6000 mass ppm or less, more preferably 5500 mass ppm or less, and further preferably 5000 mass ppm or less relative to the content of units based on all monomers in the modified PTFE. Furthermore, the content ratio is also preferably 1000 mass ppm or more and 3000 mass ppm or less.
[0018] The modified PTFE may further contain units other than the TFE unit and the PFBE unit within a range not impairing the effects of the present invention. The total content of the TFE unit and the PFBE unit is preferably 99.000% by mass or more, more preferably 99.200% by mass or more, based on the total units of the modified PTFE. The upper limit may be 100% by mass.
[0019] The thermal instability index (hereinafter also referred to as "TII") of the modified PTFE is 0-15, preferably 0-13, and more preferably 0-12. TII is generally an index of heat resistance, and a smaller TII means better heat resistance. However, as described later, it can be used as a parameter indicating the dispersibility of PFBE units in modified PTFE. The TII of modified PTFE is measured according to ASTM D4895-04.
[0020] As a method for adjusting TII within the above range, there may be mentioned a method of adjusting the amount of PFBE used during the production of modified PTFE. Another method for adjusting TII within the above range is to shorten the polymerization decay time (described later) during production of modified PTFE.
[0021] The area ratio S of the modified PTFE calculated by the following method is 0.70 or less, preferably 0.65 or less, and more preferably 0.60 or less from the viewpoint of better breaking strength of the stretched porous body. The lower limit of the area ratio S of the modified PTFE is 0.
[0022] The calculation method of the area ratio S is as follows. The modified PTFE that has no history of being heated to a temperature of 300° C. or higher is measured by a differential scanning calorimeter at a heating rate of 1° C. / min, and the obtained differential calorimetric curve is secondarily differentiated to obtain a second differential curve. In the quadratic differential curve, there is a minimum value Mi1 in the range of 19 to 21°C. A point L21 showing a maximum value on the lowest temperature side among the maximum values on the higher temperature side than the temperature showing the minimum value Mi1 and a point L22 showing a maximum value on the highest temperature side among the maximum values on the lower temperature side than the temperature showing the minimum value Mi1 are connected into a straight line, and an area S1 of a region enclosed by this straight line and the quadratic differential curve is calculated. In the quadratic differential curve, there is a minimum value Mi2 in the range of 15 to 17°C. A point L23 showing a maximum value on the lowest temperature side among the maximum values on the higher temperature side than the temperature showing the minimum value Mi2 and a point L24 showing a maximum value on the highest temperature side among the maximum values on the lower temperature side than the temperature showing the minimum value Mi2 are connected into a straight line, and an area S2 of a region enclosed by this straight line and the quadratic differential curve is calculated. The area ratio S is calculated as the ratio of the area S1 to the area S2.
[0023] Regarding the calculation method of the above area ratio S, use Figure 1 and Figure 2 Explain in more detail. Figure 1 FIG. 1 is an example of a differential calorimetry curve measured using the modified PTFE of the present invention. Figure 2FIG. 1 is an example of a second-order differential curve obtained by secondarily differentiating a differential calorimetric curve measured using the modified PTFE of the present invention. Specifically, FIG. Figure 1 The second differential curve obtained by performing the second differentiation of the differential calorimetry curve in . As a measurement procedure, a modified PTFE (10 mg) which has not been heated to a temperature of 300°C or higher is kept at -20°C for 1 minute, and then heated to 60°C at a heating rate of 1°C / min to obtain a differential calorimetric curve with the horizontal axis being the temperature and the vertical axis being the heat absorbed per unit time (refer to Figure 1 ). Then, the obtained differential calorimetric curve is subjected to secondary differentiation to obtain a secondary differential curve with the horizontal axis being the temperature and the vertical axis being the secondary differential value of the amount of heat absorbed per unit time (refer to Figure 2 ).here, Figure 2 Among them, the minimum value Mi1 is a minimum value existing in the range of 19 to 21°C, and the minimum value Mi2 is a minimum value existing in the range of 15 to 17°C. Then, in the obtained quadratic differential curve, point L21 showing a local maximum value on the lowest temperature side among the local maximum values on the higher temperature side than the temperature showing the above-mentioned local minimum value Mi1 and point L22 showing a local maximum value on the highest temperature side among the local maximum values on the lower temperature side than the temperature showing the above-mentioned local minimum value Mi1 are connected into a straight line, and the area S1 of the region enclosed by this straight line and the above-mentioned quadratic differential curve is calculated. Moreover, in the obtained quadratic differential curve, point L23 showing a local maximum value on the lowest temperature side among the local maximum values on the higher temperature side than the temperature showing the above-mentioned local minimum value Mi2 and point L24 showing a local maximum value on the highest temperature side among the local maximum values on the lower temperature side than the temperature showing the above-mentioned local minimum value Mi2 are connected into a straight line, and the area S2 of the region enclosed by this straight line and the above-mentioned quadratic differential curve is calculated. Then, the area ratio S is calculated as the ratio of the area S1 to the area S2 (area S1 / area S2). here, Figure 2 In the example, there is only one maximum value between the temperature showing the minimum value Mi1 and the temperature showing the minimum value Mi2, so point L22 and point L23 are the same point. In the case where there are two or more maximum values between the temperature showing the minimum value Mi1 and the temperature showing the minimum value Mi2, point L22 and point L23 are different points. In the above calculation method, DSC 8500 (manufactured by PERKIN ELMER) or a device compatible therewith was used as a differential scanning calorimeter. In addition, the second differential curve, area S1 and area S2 of the differential calorimetric curve were obtained by analysis software (Pyris Software, manufactured by PERKIN ELMER).
[0024] Here, it is known that a differential calorimetry curve obtained using PTFE has three peaks in the range of -20 to 60°C. The present inventors have found that if the amount of PFBE added is increased during the manufacture of modified PTFE, the positions or intensities of the three peaks will change, and it has been found that the correlation between the two peaks on the low temperature side is related to the fracture strength of the stretched porous body. Specifically, in order to make the correlation between the two peaks on the low temperature side clearer, the differential calorimetric curve obtained using the modified PTFE is secondarily differentiated, and the points corresponding to the two peaks on the low temperature side ( Figure 2 The area ratio S is calculated from the point showing the minimum value Mi1 and the point showing the minimum value Mi2 in the graph, and it is deduced that the value of the area ratio S is closely related to the fracture strength of the stretched porous body.
[0025] As a method for adjusting the area ratio S within the above range, there may be mentioned a method of adjusting the amount of PFBE used during the production of modified PTFE.
[0026] The present inventors have found that when the TII and the area ratio S of the modified PTFE satisfy the above-mentioned values, the breaking strength of the stretched porous body obtained therefrom is improved. Here, as described above, TII is an index of heat resistance, but the present inventors have found that TII is also closely related to the breaking strength of the stretched porous body obtained using the modified PTFE. More specifically, the value of TII is related to the dispersibility of the PFBE unit in the modified PTFE. When the value of TII is low, the chain portion of the PFBE unit in the modified PTFE becomes less. Therefore, TII of 15 or less substantially means that the chain portion of the PFBE unit in the modified PTFE is less than a specified amount. In the modified PTFE that meets such requirements, the chain portion of the PFBE unit is small, and the PFBE unit is introduced into the modified PTFE in a uniformly dispersed manner. As a result, it is presumed that the effect of improving the breaking strength is significantly exhibited.
[0027] From the perspective of suppressing the extrusion pressure during extrusion molding of the modified PTFE paste from being too high while further improving the breaking strength of the stretched porous body, the standard specific gravity of the modified PTFE (hereinafter also referred to as "SSG") is preferably 2.130-2.160, more preferably 2.130-2.150, further preferably 2.130-2.142, further preferably 2.130-2.141, more preferably 2.130-2.140, further preferably 2.130-2.139, and particularly preferably 2.132-2.139. SSG is a molecular weight indicator, and a larger SSG means a smaller molecular weight. The SSG can be adjusted according to the polymerization conditions when manufacturing the modified PTFE. For example, the SSG can be reduced by increasing the polymerization pressure or decreasing the polymerization temperature, or by adding PFBE (adding it at the beginning) when manufacturing the modified PTFE before the introduction of TFE. The SSG of modified PTFE is measured according to ASTM D4895-04.
[0028] From the viewpoint of handling and the like, the modified PTFE is preferably in the form of particles. The average primary particle size of modified PTFE particles is preferably more than 0.10 μm, more preferably more than 0.11 μm, further preferably more than 0.13 μm, in addition, preferably less than 0.30 μm, more preferably less than 0.25 μm, further preferably less than 0.22 μm. If the average primary particle size is more than 0.10 μm, then paste extrusion molding can be carried out under low extrusion pressure, and it is easy to obtain a molded product with no surface ripples, etc., excellent surface smoothness. If the average primary particle size is below 0.25 μm, then due to the space between particles during extrusion, it is excellent in extrusion stability, and the result is a molded product with excellent surface smoothness that is easy to obtain. The average primary particle size of modified PTFE particles is for example equivalent to the D50 measured by a laser scattering particle size distribution analyzer (trade name "LA-960V2" of Horiba Manufacturing Co., Ltd.). As described later, in an aqueous medium, when modified PTFE is manufactured, the aqueous dispersion (emulsified dispersion) of the modified PTFE particles obtained is used to implement the above-mentioned measurement, and the average primary particle size of the modified PTFE particles is obtained.
[0029] From the viewpoint of easy paste extrusion, the extrusion pressure of the modified PTFE is preferably 17 to 27 MPa, more preferably 18 to 26 MPa. The extrusion pressure is measured as follows. A sample (modified PTFE) (100 g) placed at room temperature for more than 2 hours was added to a glass bottle with a content of 500 mL, and 21.7 g of lubricating oil (ISOPAR H (registered trademark), manufactured by ExxonMobil) was added and mixed for 3 minutes to obtain a mixture. The obtained mixture was placed in a 25°C thermostatic bath for 2 hours, and then paste was extruded through an orifice with a diameter of 2.5 cm, a hole plate length of 1.1 cm, and an introduction angle of 30° at 25°C under the conditions of a reduction ratio (ratio of the cross-sectional area of the inlet of the die head to the cross-sectional area of the outlet) of 100 and an extrusion speed of 51 cm / min to obtain extruded beads (thread-like objects). The pressure required for extrusion at this time was measured, which was the extrusion pressure (unit: MPa).
[0030] The breaking strength of the modified PTFE measured under the following conditions (hereinafter also referred to as "breaking strength A") is preferably 44.7 N or more, more preferably 45.0 N or more. The breaking strength A of the modified PTFE is usually 80 N or less. The breaking strength A is measured as follows. Extruded beads were obtained in the same manner as the method for measuring the extrusion pressure, and dried at 230° C. for 30 minutes to remove the lubricant. Thereafter, the extruded beads were cut into suitable lengths, the two ends were fixed so that the clamp interval was 5.1 cm, and heated to 300° C. in an air circulation oven. Next, the beads were stretched at a stretching speed of 100% / sec and a stretching ratio of 2400% to obtain a modified PTFE stretched porous body A (hereinafter also referred to as "stretched beads A"). A total of three samples obtained from each end of the stretched bead A (if there is necking within the clamp range, it will be removed) and a sample obtained from the center of the stretched bead were measured for tensile breaking load using a tensile testing machine (manufactured by A&D Co., Ltd.), and the smallest value was taken as the breaking strength A. In the measurement of the tensile tester, the sample was clamped and fixed between movable jaws with a gauge length of 5.0 cm, and the movable jaws were driven at a speed of 300 mm / min at room temperature (24° C.) to apply tensile stress.
[0031] The breaking strength of the modified PTFE measured under the following conditions (hereinafter also referred to as "breaking strength B") is preferably 47.5 N or more, more preferably 48.0 N or more. The breaking strength B of the modified PTFE is usually 80 N or less. The breaking strength B is measured as follows. Extruded beads were obtained in the same manner as the method for measuring the extrusion pressure, and dried at 230° C. for 30 minutes to remove the lubricant. Thereafter, the extruded beads were cut into suitable lengths, the two ends were fixed so that the fastening interval was 3.8 cm, and heated to 300° C. in an air circulation oven. Next, the beads were stretched at a stretching speed of 1000% / sec and a stretching ratio of 2400% to obtain a modified PTFE stretched porous body B (hereinafter also referred to as "stretched beads B"). A total of three samples obtained from each end of the stretched bead B (if there is necking within the clamp range, it will be removed) and a sample obtained from the center of the stretched bead were measured for tensile breaking load using a tensile testing machine (manufactured by A&D Co., Ltd.), and the smallest value was taken as the breaking strength B. In the measurement of the tensile tester, the sample was clamped and fixed between movable jaws with a gauge length of 5.0 cm, and the movable jaws were driven at a speed of 300 mm / min at room temperature (24° C.) to apply tensile stress.
[0032] <Method for producing modified PTFE> The method for producing the modified PTFE is not particularly limited, and a known method can be employed. Specifically, the method for producing modified PTFE preferably includes a step of polymerizing TFE and PFBE to produce modified PTFE. From the viewpoint of the operability of the modified PTFE, the above-mentioned polymerization is preferably emulsion polymerization. In this case, it is preferred to emulsion polymerize TFE and PFBE in an aqueous medium using a polymerization initiator in the presence of an emulsifier.
[0033] In the above-mentioned steps, TFE is usually used as a main component. The main component means that the amount of TFE used is 99.000 mass %, preferably 99.400 mass % or more relative to the total mass of all monomers (the total mass of all monomers used).
[0034] In the above step, the amount of PFBE used is preferably 1000 mass ppm or more, more preferably 1500 mass ppm or more, further preferably 1700 mass ppm or more, and particularly preferably 2000 mass ppm or more relative to the total mass of all monomers. When the amount of PFBE used is 1000 mass ppm or more, more preferably 1500 mass ppm or more, the area ratio S can be easily set within the above range. The amount of PFBE units used is preferably 6000 mass ppm or less, more preferably 5500 mass ppm or less, and further preferably 5000 mass ppm or less relative to the total mass of all monomers. When the amount of PFBE used is 6000 mass ppm or less, a well-stretchable modified PTFE can be produced.
[0035] Monomers other than TFE and PFBE may be used within a range not impairing the effects of the present invention. However, from the viewpoint of more excellent effects of the present invention, the total content of TFE and PFBE is preferably 99.000% by mass or more, more preferably 99.200% by mass or more, based on the total mass of all monomers. It is even more preferred to use only TFE and PFBE.
[0036] Examples of the aqueous medium include water and a mixture of water and a water-soluble organic solvent. Specific examples of the water-soluble organic solvent include tert-butyl alcohol, propylene glycol, dipropylene glycol, dipropylene glycol monomethyl ether, and tripropylene glycol. When the aqueous medium contains a water-soluble organic solvent, the content of the water-soluble organic solvent is preferably 1 to 40 parts by mass, more preferably 3 to 30 parts by mass, based on 100 parts by mass of water.
[0037] As the emulsifier, a fluorinated anionic surfactant having a LogPOW of 2.4 to 3.4 is preferred. LogPOW is the partition coefficient between 1-octanol and water as specified in OECD Test Guidelines 107 and 117 and Japanese Industrial Standard Z7260-107 (2000). POW represents the ratio of the concentration of the surfactant in octanol to the concentration of the surfactant in water when a mixed liquid containing the surfactant to be measured is separated into octanol and water (1:1). Surfactants with large partition coefficients have a greater bioaccumulation potential, while surfactants with small partition coefficients have a smaller bioaccumulation potential. If LogPOW is less than 3.5, the bioaccumulation potential is judged to be low. In addition, when LogPOW is 2.4 or more, the stability of the aqueous emulsion of modified PTFE during polymerization can be maintained well. LogPOW is preferably 2.4 to 3.3, more preferably 2.5 to 3.3, and even more preferably 2.5 to 3.2.
[0038] From the viewpoint of bioaccumulation, it is preferred that an emulsifier having a LogPOW of 3.5 or more is not used in the method for producing modified PTFE.
[0039] Examples of the fluorinated anionic surfactant having a LogPOW of 2.4 to 3.4 include an anionic surfactant having 6 or 7 carbon atoms, 0 or 1 hydrogen atom, 0 or 1 to 4 etheric oxygen atoms, and -COOA (A represents H, NH 4 or alkali metal atom) and the remaining atoms are fluorine atoms. As specific examples of fluorinated anionic surfactants having a LogPOW of 2.4 to 3.4, preferably selected from CF 3 OCF(CF 3 )CF 2 OCF(CF 3 )COOA, CF 3 CF 2 OCF 2 CF 2 OCF 2 COOA CF 3 OCF 2 CF 2 CF 2 OCHFCF 2 COOA C 3 F 7 OCF(CF 3 )COOA, H(CF 2 CF 2 ) 3 COOA CF 3 CF 2 (CF 2 CF 2 ) 2 COOA CF 3 (CF 2 CF 2 ) 2 COOA and one or more compounds represented by the following formula (1). A represents H, NH 4 or an alkali metal atom (preferably Na or K).
[0040]
Chemical formula 1
[0041] Among these fluorinated anionic surfactants, CF 3 CF 2 OCF 2 CF 2 OCF 2 COOA, CF 3 OCF 2 CF 2 CF 2 OCHFCF 2 COOA or a compound represented by formula (1), more preferably CF 3 CF 2 OCF 2 CF 2 OCF 2 COOA. In particular, it is further preferred that A is NH 4 Fluorinated anionic surfactants.
[0042] The amount of the fluorinated anionic surfactant present (the amount used) is preferably 0.10 to 2 mass %, more preferably 0.15 to 2 mass %, and further preferably 0.20 to 2 mass % based on the final modified PTFE. If the amount of the fluorinated anionic surfactant is below 2% by mass, the modified PTFE particles are not easy to become rod-shaped, and the good stability of the aqueous emulsion is easily obtained. If the amount of the fluorinated anionic surfactant is above 0.10% by mass, the stability of the aqueous emulsion is easily obtained during polymerization, and the aggregation of the modified PTFE particles or the generation of lumps is easily prevented.
[0043] As the polymerization initiator, a water-soluble radical initiator or a water-soluble redox initiator is preferred. As the water-soluble radical initiator, persulfates such as ammonium persulfate and potassium persulfate, and water-soluble organic peroxides such as disuccinic acid peroxide, diglutaric acid peroxide, and tert-butyl hydroperoxide are preferred. As the water-soluble redox initiator, a combination of an oxidizing agent such as hydrobromic acid or its salt, hydrochloric acid or its salt, persulfuric acid or its salt, permanganic acid or its salt, hydrogen peroxide and a reducing agent such as sulfurous acid or its salt, hydrogen sulfite or its salt, thiosulfuric acid or its salt, organic acid and the like is preferred. Among them, a combination of hydrobromic acid or its salt, sulfurous acid or its salt, ammonium sulfite, and a combination of permanganic acid or its salt, potassium permanganate and oxalic acid are more preferred. As the polymerization initiator, a mixed system of a persulfate and disuccinic acid peroxide is preferred, and a mixed system of ammonium persulfate and disuccinic acid peroxide is more preferred. The polymerization initiator may be used alone or in combination of two or more.
[0044] The amount of the polymerization initiator used is preferably 1 to 100 ppm by mass, more preferably 3 to 80 ppm by mass, based on the total amount of TFE used for polymerization.
[0045] It is preferred to use a stabilizing aid in emulsion polymerization. The stabilizing aid preferably has sufficient hydrophobicity and can be easily separated and removed from the aqueous emulsion of modified PTFE after emulsion polymerization. As the stabilizing aid, paraffin wax, fluorinated oil, fluorinated solvent, and silicone oil are preferred, and paraffin wax is more preferred. The stabilizing aid may be used alone or in combination of two or more. Paraffin wax may be liquid, semisolid or solid at room temperature, but is preferably a saturated hydrocarbon having at least 16 carbon atoms. The melting point of paraffin wax is preferably 40 to 65°C, more preferably 50 to 65°C. The amount of the stabilizing agent used is preferably 0.1 to 12% by mass, more preferably 0.1 to 8% by mass, relative to the aqueous medium used. If it is above the lower limit of the above range, it is easy to obtain good stability of the aqueous emulsion of modified PTFE during polymerization. If it is below the upper limit, it is easy to separate and remove the stabilizing agent after polymerization.
[0046] TFE is preferably supplied to the polymerization reactor continuously or intermittently so that the polymerization pressure reaches a prescribed pressure. In the case of PFBE, the polymerization initiator may be added to the polymerization reactor all at once or in portions, but is preferably added to the polymerization reactor all at once before supplying TFE to the polymerization reactor. When a polymerization initiator is used, the polymerization initiator may be added to the polymerization reactor all at once or in portions. When an emulsifier is used, the emulsifier may be added to the polymerization reactor all at once or in portions. However, it is preferably added all at once because the modified PTFE in the obtained aqueous emulsion can be easily coagulated.
[0047] As a preferred embodiment of the method for producing modified PTFE of the present invention, embodiment A including steps 1 to 7 in this order may be mentioned. (Step 1) A step of adding components other than monomers (aqueous medium, emulsifier, stabilizing aid, polymerization initiator, etc.) to a polymerization reactor (Step 2) A step of adding the entire amount of PFBE used for polymerization to the polymerization reactor after reducing the pressure in the polymerization reactor. (Step 3) A step of supplying TFE so that the pressure in the polymerization reactor reaches a predetermined value (e.g., 0.01 to 4.0 MPa) and then heating the polymerization reactor until the temperature reaches a predetermined value (e.g., 10 to 95° C.) (Step 4) A step of continuously adding a polymerization initiator after supplying TFE so that the pressure in the polymerization reactor becomes higher than the pressure set in step 3 (for example, 0.1 to 4.1 MPa). (Step 5) A step of restarting the supply of TFE at a time point when the pressure in the polymerization reactor is reduced by 0.02 MPa and intermittently supplying TFE so that the pressure in the polymerization reactor is maintained at a predetermined value (e.g., 0.5 to 4.0 MPa) (Step 6) A step of stopping the addition of the polymerization initiator when the total amount of TFE added reaches a predetermined amount (for example, 10 to 90% by mass relative to the total amount of TFE used for polymerization) (Step 7) Step of supplying TFE until a preset addition amount is reached
[0048] Furthermore, as another suitable embodiment, embodiment B including step 1, (step 2-2), (step 3-2), (step 4-2), (step 5), (step 6), and step 7 in this order can be mentioned. (Step 1) A step of adding components other than monomers (aqueous medium, emulsifier, stabilizing aid, polymerization initiator, etc.) to a polymerization reactor (Step 2-2) A step of reducing the pressure in the polymerization reactor and then heating the polymerization reactor until the temperature reaches a predetermined temperature (e.g., 10 to 95° C.) (Step 3-2) Step of adding the entire amount of PFBE used for polymerization to a polymerization reactor (Step 4-2) A step of continuously adding a polymerization initiator after supplying TFE so that the pressure in the polymerization reactor reaches a predetermined value (e.g., 0.5 to 4.0 MPa) (Step 5) A step of restarting the supply of TFE at a time point when the pressure in the polymerization reactor is reduced by 0.02 MPa and intermittently supplying TFE so that the pressure in the polymerization reactor is maintained at a predetermined value (e.g., 0.5 to 4.0 MPa) (Step 6) A step of stopping the addition of the polymerization initiator when the total amount of TFE added reaches a predetermined amount (for example, 10 to 90% by mass relative to the total amount of TFE used for polymerization) (Step 7) Step of supplying TFE until a preset addition amount is reached
[0049] It is considered that the polymerization of PFBE and TFE proceeds until the pressure in the polymerization reactor is reduced by 0.02 MPa in the above step 5. It is also considered that the total amount of PFBE is almost consumed at the time when the pressure in the polymerization reactor is reduced by 0.02 MPa in the above step 5. It is considered that after the total amount of PFBE is almost consumed, TFE begins to be consumed rapidly. In this specification, the time from the time when TFE was supplied to the polymerization reactor in the above steps 4 and 4-2 to the time when the pressure in the polymerization reactor was reduced by 0.02 MPa in the above step 5 is referred to as "polymerization reduction time". The polymerization decline time is preferably 100 minutes or less, more preferably 80 minutes or less, and further preferably 60 minutes or less. When the polymerization decline time is 100 minutes or less, TII can be easily set within the above range. Examples of methods for adjusting the polymerization fall time include adjustment of the polymerization temperature, adjustment of the polymerization pressure, adjustment of the polymerization initiator addition rate, and adjustment of the total amount of the polymerization initiator used.
[0050] The polymerization time in Form A and Form B refers to the time from the end time of the polymerization decline time (i.e., the time when the pressure in the polymerization reactor is reduced by 0.02 MPa in the above step 5) to the time when TFE is supplied to a predetermined addition amount in step 7. The polymerization time in Form A and Form B is preferably 40 to 480 minutes, more preferably 60 to 420 minutes, and even more preferably 80 to 360 minutes.
[0051] By carrying out steps 1 to 7 in embodiment A, an emulsified dispersion in which modified PTFE is dispersed in the form of particles (emulsified dispersion containing modified PTFE particles) can be obtained. The concentration of the modified PTFE particles in the emulsified dispersion is preferably 10 to 45% by mass, more preferably 15 to 45% by mass, and further preferably 15 to 43% by mass. Within the above range, the modified PTFE particles in the emulsified dispersion can be coagulated more easily and the turbidity of the coagulated liquid can be suppressed. The suitable range of the average primary particle size of the modified PTFE particles is as described above.
[0052] <Modified PTFE powder> As a method for obtaining a modified PTFE powder (modified PTFE fine powder) composed of modified PTFE particles from an emulsified dispersion obtained by emulsion polymerization, a known method can be used. For example, after diluting the emulsion dispersion containing modified PTFE particles with water so that the concentration of modified PTFE reaches 8 to 25 mass % and adjusting the temperature of the emulsion dispersion to 5 to 35° C., the emulsion dispersion is vigorously stirred to cause agglomeration. At this time, the pH value can be adjusted as needed. In addition, an agglomeration aid such as an electrolyte or a water-soluble organic solvent can also be added to the emulsion dispersion. Thereafter, the agglomerated modified PTFE particles are separated from water by appropriate stirring, and the obtained wet powder (wet fine powder) is granulated and sized as required, and then dried as required, thereby obtaining a modified PTFE powder.
[0053] The drying is performed in a state where the wet powder hardly flows, preferably while being left to stand. Examples of the drying method include vacuum drying, high-frequency drying, and hot air drying. The drying temperature is preferably 10 to 300°C, more preferably 100 to 250°C.
[0054] <Molding> The modified PTFE can be suitably used for paste extrusion molding. The desired molded product (molded article) can be obtained by extrusion molding a modified PTFE (particularly modified PTFE powder) paste. Paste extrusion molding is a method of mixing modified PTFE powder and a lubricant to make the modified PTFE powder fluid, and then extruding and molding it into a molded product such as a film or a tube. The mixing ratio of the lubricant can be appropriately selected so that the modified PTFE powder has fluidity. For example, when the total amount of the modified PTFE powder and the lubricant is 100 mass %, it is preferably 10 to 30 mass %, and more preferably 15 to 20 mass %. As the lubricant, for example, naphtha or a petroleum hydrocarbon having a dry point of 100° C. or higher is preferable. The mixture may be added with additives such as pigments for the purpose of coloring, and various fillers may be added for the purpose of imparting strength, conductivity, etc.
[0055] Examples of the shape of the molded product include a tube, a sheet, a film, and a fiber. Examples of the application include a tube, a wire coating, a sealing material, a porous membrane, and a filter. Alternatively, the modified PTFE powder paste is extruded to obtain extruded beads, and the extruded beads are stretched to obtain a stretched porous body of modified PTFE. Stretching conditions include, for example, a speed of 5 to 1000% / sec and a stretching ratio of 500% or more. Examples of the shape of the article composed of the stretched porous body include a tube shape, a sheet shape, a film shape, and a fiber shape. Example
[0056] Hereinafter, the present invention will be described in detail with reference to examples. Examples 1 to 5 are comparative examples, and Examples 6 to 14 are embodiments. However, the present invention is not limited to these examples. Various measurement methods and evaluation methods are as follows. (A) Average primary particle size (nm) of modified PTFE particles (hereinafter also referred to as "PPS") The aqueous dispersion of modified PTFE particles was used as a sample and the particle size distribution was measured using a laser scattering particle size analyzer (trade name "LA-960V2" manufactured by Horiba, Ltd.).
[0057] (B) Standard specific gravity (hereinafter also referred to as "SSG") The measurement was carried out according to ASTM D4895-04. Weigh 12.0g of the sample (modified PTFE powder) and compress it in a cylindrical mold with an inner diameter of 28.6mm to obtain a granular sample. Put it in an oven at 290°C and heat it at 120°C / hour. Further, after keeping it at 380°C for 30 minutes, cool it at 60°C / hour and keep it at 294°C for 24 minutes. After keeping the sample in a dryer at 23°C for 12 hours, measure the specific gravity of the sample relative to water at 23°C, which is the standard specific gravity. The smaller the SSG value, the larger the molecular weight.
[0058] (C) Thermal instability index (hereinafter also referred to as "TII") The measurement was performed according to ASTM D4895-04. The preparation of the extended specific gravity (hereinafter also referred to as "ESG") sample was performed in the same manner as the above-mentioned SSG except that the holding time at 380° C. was changed from 30 minutes to 360 minutes. The calculation is performed as TII=(ESG-SSG)×1000. A small TII value means that the molecular weight does not change when the holding time at 380° C. is prolonged, which means that the heat resistance is excellent.
[0059] (D) Extrusion pressure (hereinafter also referred to as "EP") Powder (modified PTFE) (100 g) left at room temperature for more than 2 hours was added to a glass bottle with a content of 500 mL, and lubricating oil (ISOPAR H (registered trademark), manufactured by ExxonMobil) (21.7 g) was added and mixed for 3 minutes to obtain a mixture. The obtained mixture was placed in a 25°C thermostatic bath for 2 hours, and then paste was extruded at 25°C through an orifice with a diameter of 2.5 cm, a hole plate length of 1.1 cm, and an introduction angle of 30° under the conditions of a reduction ratio (ratio of the cross-sectional area of the inlet of the die head to the cross-sectional area of the outlet) of 100 and an extrusion speed of 51 cm / min to obtain extruded beads (threads). The pressure required for extrusion at this time was measured, which was the extrusion pressure (unit: MPa).
[0060] (E) Breaking strength Breaking strength A Extruded beads were obtained in the same manner as in the measurement of the extrusion pressure, and dried at 230° C. for 30 minutes to remove the lubricant. Thereafter, the extruded beads were cut into suitable lengths, the two ends were fixed so that the fastening interval was 5.1 cm, and heated to 300° C. in an air circulation oven. Next, the beads were stretched at a stretching speed of 100% / sec and a stretching ratio of 2400% to obtain a modified PTFE stretched porous body A (hereinafter also referred to as "stretched beads A"). A total of three samples obtained from each end of the stretched bead A (if there is necking within the clamp range, it will be removed) and a sample obtained from the center of the stretched bead were measured for tensile breaking load using a tensile testing machine (manufactured by A&D Co., Ltd.), and the smallest value was taken as the breaking strength A. In the measurement of the tensile tester, the sample was clamped and fixed between movable jaws with a gauge length of 5.0 cm, and the movable jaws were driven at a speed of 300 mm / min at room temperature (24° C.) to apply tensile stress.
[0061] Breaking strength B Extruded beads were obtained in the same manner as the method for measuring the extrusion pressure, and dried at 230° C. for 30 minutes to remove the lubricant. Thereafter, the extruded beads were cut into suitable lengths, the two ends were fixed so that the fastening interval was 3.8 cm, and heated to 300° C. in an air circulation oven. Next, the beads were stretched at a stretching speed of 1000% / sec and a stretching ratio of 2400% to obtain a modified PTFE stretched porous body B (hereinafter also referred to as "stretched beads B"). A total of three samples obtained from each end of the stretched bead B (if there is necking within the clamp range, it will be removed) and a sample obtained from the center of the stretched bead were measured for tensile breaking load using a tensile testing machine (manufactured by A&D Co., Ltd.), and the smallest value was taken as the breaking strength B. In the measurement of the tensile tester, the sample was clamped and fixed between movable jaws with a gauge length of 5.0 cm, and the movable jaws were driven at a speed of 300 mm / min at room temperature (24° C.) to apply tensile stress.
[0062] When the breaking strength A is 44.7 N or more and the breaking strength B is 47.5 N or more, it is judged that a stretched porous body excellent in breaking strength is obtained.
[0063] (F) Area ratio S The measurement was performed using a differential scanning calorimeter (DSC 8500, manufactured by PERKIN ELMER) that had been temperature-calibrated in advance using indium and zinc as standard samples. The modified PTFE that had not been heated to 300°C or higher was standardized to a sample amount of 10 mg, kept at -20°C for 1 minute, and then heated to 60°C at a heating rate of 1°C / min to obtain a differential calorimetry curve. The obtained differential calorimetric curve is secondarily differentiated to obtain a second differential curve with the horizontal axis representing the temperature and the vertical axis representing the second differential value of the amount of heat absorbed per unit time. Then, in the obtained quadratic differential curve, point L21 showing a local maximum value on the lowest temperature side among the local maximum values on the higher temperature side than the temperature showing the local minimum value Mi1 in the range of 19 to 21°C and point L22 showing a local maximum value on the highest temperature side among the local maximum values on the lower temperature side than the temperature showing the above-mentioned local minimum value Mi1 are connected into a straight line, and the area S1 of the region enclosed by this straight line and the above-mentioned quadratic differential curve is calculated. Moreover, in the obtained quadratic differential curve, point L23 showing a local maximum value on the lowest temperature side among the local maximum values on the higher temperature side than the temperature showing the local minimum value Mi2 in the range of 15 to 17°C and point L24 showing a local maximum value on the highest temperature side among the local maximum values on the lower temperature side than the temperature showing the above-mentioned local minimum value Mi2 are connected into a straight line, and the area S2 of the region enclosed by this straight line and the above-mentioned quadratic differential curve is calculated. Then, the area ratio S is calculated as the ratio of the area S1 to the area S2 (area S1 / area S2). In addition, the second differential curve of the differential calorimetry curve, the area S1, and the area S2 were obtained by using analysis software (Pyris Software, manufactured by PERKIN ELMER).
[0064] (G) Stability test of aqueous emulsion (determination of stability retention time) Two interference plates (baffles) with a thickness of 2.9 mm, a width of 2.5 cm, and a length of 15 cm were welded to the inner wall of a cylindrical container made of SUS304 and with an inner diameter of 12 cm in a manner symmetrical to the central axis of the cylindrical container. The distance from the bottom surface of the cylindrical container to the lower end of the interference plate was 2.5 cm. In addition, a stirring wing with two paddles installed on a shaft with an inner diameter of 8.0 mm was provided in the cylindrical container. The paddles had a thickness of 1.2 mm, a width of 1.3 cm, and a length of 9.7 cm. The inclination angle of the paddles relative to the surface perpendicular to the axial direction of the shaft was 30°, and the distance from the bottom surface of the cylindrical container to the lower end of the paddles was 5 mm. The solid content concentration of the aqueous emulsion was prepared to 20% by mass and 800 g was put into a cylindrical container, and the temperature was adjusted to 23±1°C. Then, the stirring blade was rotated at 500 rpm to stir, and the time from the start of stirring to the destruction of the aqueous emulsion and the aggregation of the modified PTFE particles in the aqueous emulsion was measured, which was the stability retention time (unit: seconds). The aggregation time point was determined by visually confirming the change in the stirring sound and the generation of wet powder.
[0065] In addition, the solid content concentration of the aqueous emulsion was determined as follows. 7-8 g of modified PTFE aqueous emulsion was weighed in an aluminum dish whose mass was measured in advance, and heated at 120°C for 2 hours to evaporate the water. Then, the mass of the aluminum dish including the solid content remaining on the aluminum dish was measured. The solid content concentration was calculated by dividing the mass of the solid content by the mass of the aqueous emulsion used.
[0066] (Example 1) After the polymerization reaction started, the specified polymerization pressure was maintained until the polymerization reaction was completed, and the total amount of TFE added, 22.5 kg, was estimated as the final amount of modified PTFE produced, and the amount of PFBE added was set to 400 ppm thereof, i.e., 9 g. In addition, the amount of the fluorinated anionic surfactant added was set to about 1.32 mass % of the final amount of modified PTFE produced, i.e., 243 g. In a 100L stainless steel autoclave equipped with an interference plate and a stirrer, C as a fluorinated anionic surfactant was added. 2 F 5 OC 2 F 4 OCF 2 COONH 4 50 g of ammonium perfluoro-3,6-dioxooctanoate, LogPOW=3.1, hereinafter also referred to as "APFDO"), 846 g of paraffin as a stabilizing aid, 20.0 g of succinic acid, 0.299 g (0.56 mmol / L) of oxalic acid, and 59.4 L of deionized water (Step 1). After nitrogen substitution in the autoclave, the pressure was reduced and 9.0 g of PFBE was added all at once (step 2). Thereafter, the pressure was increased to about 0.1 MPa with TFE and the temperature was raised to 70° C. (initial polymerization temperature) while stirring (step 3). Thereafter, TFE was introduced and the pressure was increased to 1.618 MPaG. When the pressure reached 1.618 MPaG, the addition of TFE was stopped, and a 0.37 g / L potassium permanganate aqueous solution was continuously added at 4 mL / min (step 4). Subsequently, when the pressure inside the autoclave was reduced by 0.02 MPa, TFE was added so that the pressure inside the autoclave was maintained at 1.618 MPaG to carry out polymerization (step 5). Here, the time from the time when TFE was supplied to the autoclave in the above step 4 to the time when the pressure inside the autoclave was reduced by 0.02 MPa in the above step 5 was the polymerization decline time, and the polymerization decline time was 33.4 minutes. When the amount of TFE added reached 9.0 kg after the start of polymerization, the addition of the potassium permanganate aqueous solution was stopped, and 193 g of APFDO was additionally added (step 6). The total amount of potassium permanganate added was 96 mg. From the time when the addition of the potassium permanganate aqueous solution was stopped, the temperature was raised to 90°C (final polymerization temperature) at a ratio of 30°C / time, and the polymerization reaction was terminated at a time point when the amount of TFE added reached 22.5 kg after the start of polymerization, and the TFE in the autoclave was discharged into the atmosphere (step 7). Here, when the time point when the polymerization decline time ended was defined as the starting point of the polymerization reaction (the starting time point of the polymerization time), and the time point when the amount of TFE added reached 22.5 kg was defined as the end point of the polymerization reaction (the ending time point of the polymerization time), the polymerization time was 153 minutes.
[0067] The obtained modified PTFE aqueous emulsion was cooled and the supernatant paraffin was removed. The solid content concentration of the modified PTFE aqueous emulsion was 25.5% by mass. The yield of the modified PTFE was 20.9 kg. In addition, the coagulated material in the autoclave was traceable. In addition, based on 20.9 kg of the obtained modified PTFE, the added amount of PFBE (9.0 g) is 430 mass ppm. Therefore, the content ratio of the PFBE unit is 430 mass ppm relative to the content of the units based on all monomers in the obtained modified PTFE.
[0068] The modified PTFE aqueous emulsion thus obtained was used to measure PPS and stability retention time by the above-mentioned method. The results are shown in Table 1.
[0069] Furthermore, the obtained modified PTFE aqueous emulsion was diluted with deionized water to a concentration of 10% by mass, adjusted to 20° C., and ammonium carbonate was added and stirred to agglomerate to obtain a wet powder. Thereafter, the wet powder was dried at 150° C. for 14.5 hours in an atmosphere of an aqueous ammonium carbonate solution to obtain a modified PTFE fine powder (modified PTFE powder). SSG, TII, extrusion pressure, breaking strength A, breaking strength B and area ratio S were measured by the above-mentioned methods. The results are shown in Table 1.
[0070] (Example 2) A modified PTFE aqueous emulsion and modified PTFE fine powder (modified PTFE powder) were obtained in the same manner as in Example 1, except that the amount of PFBE added in step 2 was changed to 22.5 g, the total amount of potassium permanganate added was changed to 135 mg, and the drying conditions during the production of the PTFE fine powder (modified PTFE powder) were changed to 160° C. for 10 hours. The solid content concentration of the obtained modified PTFE aqueous emulsion was 24.9% by mass, and the yield of modified PTFE was 20.4 kg. In addition, based on 20.4 kg of the obtained modified PTFE, the added amount of PFBE (22.5 g) is 1100 mass ppm. Therefore, the content ratio of the PFBE unit relative to the content of the units based on all monomers in the obtained modified PTFE is 1100 mass ppm. The above-mentioned measurements were carried out using the obtained modified PTFE aqueous emulsion and modified PTFE fine powder (modified PTFE powder).
[0071] (Example 3) A modified PTFE aqueous emulsion and modified PTFE fine powder (modified PTFE powder) were obtained in the same manner as in Example 2, except that the amount of PFBE added in step 2 was changed to 67.5 g, the total amount of potassium permanganate added was changed to 433 mg, and the pressure in step 4 was changed to 1.860 MPaG. The solid content concentration of the obtained modified PTFE aqueous emulsion was 22.9% by mass, and the yield of modified PTFE was 18.5 kg. In addition, based on 18.5 kg of the obtained modified PTFE, the added amount of PFBE (67.5 g) is 3650 mass ppm. Therefore, the content ratio of the PFBE unit is 3650 mass ppm relative to the content of the units based on all monomers in the obtained modified PTFE. The above-mentioned measurements were carried out using the obtained modified PTFE aqueous emulsion and modified PTFE fine powder (modified PTFE powder).
[0072] (Example 4) A modified PTFE aqueous emulsion and modified PTFE fine powder (modified PTFE powder) were obtained in the same manner as in Example 3, except that the amount of PFBE added in step 2 was changed to 90.0 g, the concentration of the potassium permanganate aqueous solution in step 4 was changed to 0.74 g / L, the total amount of potassium permanganate added was changed to 758 mg, and the heating temperature (initial polymerization temperature) in step 3 was changed to 80° C. The solid content concentration of the obtained modified PTFE aqueous emulsion was 23.1% by mass, and the yield of modified PTFE was 18.6 kg. In addition, based on 18.6 kg of the obtained modified PTFE, the added amount of PFBE (90.0 g) is 4830 mass ppm. Therefore, the content ratio of the PFBE unit relative to the content of the units based on all monomers in the obtained modified PTFE is 4830 mass ppm. The above-mentioned measurements were carried out using the obtained modified PTFE aqueous emulsion and modified PTFE fine powder (modified PTFE powder).
[0073] (Example 5) A modified PTFE aqueous emulsion and modified PTFE fine powder (modified PTFE powder) were obtained in the same manner as in Example 4, except that the concentration of the potassium permanganate aqueous solution in step 4 was changed to 1.48 g / L and the total amount of potassium permanganate added was changed to 790 mg. The solid content concentration of the obtained modified PTFE aqueous emulsion was 18.7% by mass, and the yield of modified PTFE was 14.2 kg. In addition, based on 14.2 kg of the obtained modified PTFE, the added amount of PFBE (90.0 g) was 6330 mass ppm. Therefore, the content ratio of the PFBE unit relative to the content of the units based on all monomers in the obtained modified PTFE was 6330 mass ppm. The above-mentioned measurements were carried out using the obtained modified PTFE aqueous emulsion and modified PTFE fine powder (modified PTFE powder).
[0074] (Example 6) A modified PTFE aqueous emulsion and modified PTFE fine powder (modified PTFE powder) were obtained in the same manner as in Example 5, except that the amount of PFBE added in step 2 was changed to 51.8 g, the concentration of the potassium permanganate aqueous solution in step 4 was changed to 3.7 g / L, and the total amount of potassium permanganate added was changed to 481 mg. The solid content concentration of the obtained modified PTFE aqueous emulsion was 22.9% by mass, and the yield of modified PTFE was 18.2 kg. Moreover, based on 18.2 kg of the obtained modified PTFE, the added amount of PFBE (51.8 g) was 2840 mass ppm. Therefore, the content ratio of the PFBE unit relative to the content of the units based on all monomers in the obtained modified PTFE was 2840 mass ppm. The above-mentioned measurements were carried out using the obtained modified PTFE aqueous emulsion and modified PTFE fine powder (modified PTFE powder).
[0075] (Example 7) A modified PTFE aqueous emulsion and modified PTFE fine powder (modified PTFE powder) were obtained in the same manner as in Example 6, except that the amount of PFBE added in step 2 was changed to 67.7 g and the total amount of potassium permanganate added was changed to 651 mg. The solid content concentration of the obtained modified PTFE aqueous emulsion was 22.3% by mass, and the yield of modified PTFE was 17.6 kg. Moreover, based on 17.6 kg of the obtained modified PTFE, the added amount of PFBE (67.7 g) was 3850 mass ppm. Therefore, the content ratio of the PFBE unit relative to the content of the units based on all monomers in the obtained modified PTFE was 3850 mass ppm. The above-mentioned measurements were carried out using the obtained modified PTFE aqueous emulsion and modified PTFE fine powder (modified PTFE powder).
[0076] (Example 8) A modified PTFE aqueous emulsion and modified PTFE fine powder (modified PTFE powder) were obtained in the same manner as in Example 7, except that the amount of PFBE added in step 2 was changed to 51.8 g, the total amount of potassium permanganate added was changed to 444 mg, and the drying conditions during the production of the PTFE fine powder (modified PTFE powder) were changed to 7.1 hours at 205°C. The solid content concentration of the obtained modified PTFE aqueous emulsion was 22.4% by mass, and the yield of modified PTFE was 17.7 kg. Moreover, based on 17.7 kg of the obtained modified PTFE, the added amount of PFBE (51.8 g) was 2930 mass ppm. Therefore, the content ratio of the PFBE unit relative to the content of the units based on all monomers in the obtained modified PTFE was 2930 mass ppm. The above-mentioned measurements were carried out using the obtained modified PTFE aqueous emulsion and modified PTFE fine powder (modified PTFE powder).
[0077] (Example 9) A modified PTFE aqueous emulsion and modified PTFE fine powder (modified PTFE powder) were obtained in the same manner as in Example 8, except that succinic acid was not used in step 1 and the total amount of potassium permanganate added was changed to 403 mg. The solid content concentration of the obtained modified PTFE aqueous emulsion was 21.9% by mass, and the yield of modified PTFE was 17.2 kg. Moreover, based on 17.2 kg of the obtained modified PTFE, the added amount of PFBE (51.8 g) was 3020 mass ppm. Therefore, the content ratio of the PFBE unit relative to the content of the units based on all monomers in the obtained modified PTFE was 3020 mass ppm. The above-mentioned measurements were carried out using the obtained modified PTFE aqueous emulsion and modified PTFE fine powder (modified PTFE powder).
[0078] (Example 10) A modified PTFE aqueous emulsion and modified PTFE fine powder (modified PTFE powder) were obtained in the same manner as in Example 9, except that APFDO was not additionally added in step 6 and the total amount of potassium permanganate added was changed to 396 mg. The solid content concentration of the obtained modified PTFE aqueous emulsion was 21.7% by mass, and the yield of modified PTFE was 17.1 kg. Moreover, based on 17.1 kg of the obtained modified PTFE, the added amount of PFBE (51.8 g) was 3040 mass ppm. Therefore, the content ratio of the PFBE unit relative to the content of the units based on all monomers in the obtained modified PTFE was 3040 mass ppm. The above-mentioned measurements were carried out using the obtained modified PTFE aqueous emulsion and modified PTFE fine powder (modified PTFE powder).
[0079] In Table 1, "Potassium permanganate addition rate per TFE mass" refers to the ratio (unit: mg / g / min) of the potassium permanganate addition rate (1.48 mg / min in Example 1) to the amount of TFE added up to step 6 (9.0 kg=9000 g in Example 1).
[0080] [Table 1]
[0081] (Example 11) After the polymerization reaction started, the specified polymerization pressure was maintained until the polymerization reaction was completed. At the same time, the total amount of TFE added, 20.45 kg, was estimated as the final amount of modified PTFE produced, and the amount of PFBE added was set to 2000 ppm thereof, i.e., 40.90 g. In a 100L stainless steel autoclave equipped with an interference plate and a stirrer, add the fluorinated anionic surfactant C 2 F 5 OC 2 F 4 OCF 2 COONH 4 50.23 g of ammonium perfluoro-3,6-dioxooctanoate, LogPOW=3.1, hereinafter also referred to as "APFDO"), 846 g of paraffin as a stabilizing aid, 20.0 g of succinic acid, 2.99 g (5.60 mmol / L) of oxalic acid, and 59.4 L of deionized water (Step 1). After replacing the autoclave with nitrogen, the pressure was reduced and the temperature was raised to 65° C. (initial polymerization temperature) and stirred (step 2-2). Thereafter, the entire amount of PFBE used for polymerization was added to the polymerization reactor (step 3-2), and then TFE was introduced and the pressure was increased to 1.660 MPaG. When the pressure reached 1.660 MPaG, the addition of TFE was stopped, and a 0.8 g / L potassium permanganate aqueous solution was continuously added at 10.5 mL / min (step 4-2). Then, when the pressure inside the autoclave was reduced by 0.02 MPa, TFE was added so that the pressure inside the electric furnace was maintained at 1.660 MPaG to carry out polymerization (step 5). Here, the time from the time when TFE was supplied to the autoclave in the above step 4 to the time when the pressure inside the autoclave was reduced by 0.02 MPa in the above step 5 was the polymerization decline time, and the polymerization decline time was 26.1 minutes. When the amount of TFE added reached 9.95 kg after the start of polymerization, the addition of the potassium permanganate aqueous solution was stopped (step 6). The total amount of potassium permanganate added was 398 mg. From the time when the addition of the potassium permanganate aqueous solution was stopped, the temperature was raised to 90°C (final polymerization temperature) at a ratio of 30°C / time, and the polymerization reaction was terminated at a time point when the amount of TFE added reached 20.50 kg after the start of polymerization, and the TFE in the autoclave was discharged into the atmosphere (step 7). Here, when the time point when the polymerization decline time ended was defined as the starting point of the polymerization reaction (the starting time point of the polymerization time), and the time point when the amount of TFE added reached 20.50 kg was defined as the end point of the polymerization reaction (the ending time point of the polymerization time), the polymerization time was 121 minutes.
[0082] The obtained modified PTFE aqueous emulsion was cooled and the supernatant paraffin was removed. The solid content concentration of the modified PTFE aqueous emulsion was 24.0% by mass. The yield of the modified PTFE was 20.4 kg. In addition, the coagulated material in the autoclave was traceable. Moreover, based on 20.4 kg of the obtained modified PTFE, the added amount of PFBE (40.90 g) was 2811 mass ppm. Therefore, the content ratio of the PFBE unit relative to the content of the units based on all monomers in the obtained modified PTFE was 2811 mass ppm.
[0083] The obtained modified PTFE aqueous emulsion was used to measure PPS and stability retention time by the above-mentioned method. The results are shown in Table 2.
[0084] Furthermore, the obtained modified PTFE aqueous emulsion was diluted with deionized water to a concentration of 10% by mass, adjusted to 13° C., and stirred to agglomerate to obtain a wet powder. Thereafter, the wet powder was dried at 205° C. for 7.1 hours in an atmosphere of an aqueous ammonium carbonate solution to obtain a modified PTFE fine powder (modified PTFE powder). SSG, TII, extrusion pressure, breaking strength A, breaking strength B and area ratio S were measured by the above-mentioned methods. The results are shown in Table 2.
[0085] (Example 12) A modified PTFE aqueous emulsion and modified PTFE fine powder (modified PTFE powder) were obtained in the same manner as in Example 1, except that the amount of PFBE added in step 2 was changed to 30.68 g and the total amount of potassium permanganate added was changed to 274 mg. The solid content concentration of the obtained modified PTFE aqueous emulsion was 24.3% by mass, and the yield of modified PTFE was 19.8 kg. Moreover, based on 19.8 kg of the obtained modified PTFE, the added amount of PFBE (30.68 g) was 1552 mass ppm. Therefore, the content ratio of the PFBE unit relative to the content of the units based on all monomers in the obtained modified PTFE was 1552 mass ppm. The above-mentioned measurements were carried out using the obtained modified PTFE aqueous emulsion and modified PTFE fine powder (modified PTFE powder).
[0086] (Example 13) A modified PTFE aqueous emulsion and modified PTFE fine powder (modified PTFE powder) were obtained in the same manner as in Example 1, except that the amount of PFBE added in step 2 was changed to 20.45 g and the total amount of potassium permanganate added was changed to 149.6 mg. The solid content concentration of the obtained modified PTFE aqueous emulsion was 24.1% by mass, and the yield of modified PTFE was 19.58 kg. Moreover, based on 19.58 kg of the obtained modified PTFE, the added amount of PFBE (20.45 g) was 1044 mass ppm. Therefore, the content ratio of the PFBE unit relative to the content of the units based on all monomers in the obtained modified PTFE was 1044 mass ppm. The above-mentioned measurements were carried out using the obtained modified PTFE aqueous emulsion and modified PTFE fine powder (modified PTFE powder).
[0087] (Example 14) A modified PTFE aqueous emulsion and modified PTFE fine powder (modified PTFE powder) were obtained in the same manner as in Example 1, except that the amount of PFBE added in step 2 was changed to 25.56 g and the total amount of potassium permanganate added was changed to 163.2 mg. The solid content concentration of the obtained modified PTFE aqueous emulsion was 24.0% by mass, and the yield of modified PTFE was 19.47 kg. Moreover, based on 19.47 kg of the obtained modified PTFE, the added amount of PFBE (20.45 g) was 1313 mass ppm. Therefore, the content ratio of the PFBE unit relative to the content of the units based on all monomers in the obtained modified PTFE was 1313 mass ppm. The above-mentioned measurements were carried out using the obtained modified PTFE aqueous emulsion and modified PTFE fine powder (modified PTFE powder).
[0088] [Table 2]
[0089] As shown in Tables 1 and 2, when the thermal instability index (TII) of the modified PTFE containing TFE units and PFBE units is 0 to 15 and the area ratio S is 0.70 or less, it was confirmed that a stretched porous body having excellent breaking strength can be produced (Examples 6 to 14). In addition, the entire contents of the specification, claims, drawings, and abstract of Japanese Patent Application No. 2022-114814 filed on Jul. 19, 2022 are cited here as a disclosure of the present invention. Explanation of symbols
[0090] Mi1, Mi2 minimum L21, L22, L23, L24 points S1, S2 area
Claims
1. A modified polytetrafluoroethylene, The modified polytetrafluoroethylene comprises units based on tetrafluoroethylene and units based on the following other monomers copolymerizable with tetrafluoroethylene, wherein: The thermal instability index is 0 to 15. The area ratio S calculated by the following method is less than 0.70; Other monomers: At least one selected from perfluoro(alkyl vinyl ether), hexafluoropropylene, and fluoroalkylethylene; Calculation method of area ratio S: The modified polytetrafluoroethylene which has not been heated to a temperature of 300° C. or higher is measured by a differential scanning calorimeter at a heating rate of 1° C. / min, and the obtained differential calorimetric curve is secondarily differentiated to obtain a second differential curve. There is a minimum value Mi1 in the range of 19 to 21°C in the quadratic differential curve. A point L21 showing a maximum value on the lowest temperature side among the maximum values on the higher temperature side than the temperature showing the minimum value Mi1 and a point L22 showing a maximum value on the highest temperature side among the maximum values on the lower temperature side than the temperature showing the minimum value Mi1 are connected into a straight line, and an area S1 of a region enclosed by this straight line and the quadratic differential curve is calculated. There is a minimum value Mi2 in the range of 15 to 17°C in the quadratic differential curve. A point L23 showing a maximum value on the lowest temperature side among the maximum values on the higher temperature side than the temperature showing the minimum value Mi2 and a point L24 showing a maximum value on the highest temperature side among the maximum values on the lower temperature side than the temperature showing the minimum value Mi2 are connected into a straight line, and an area S2 of a region enclosed by this straight line and the quadratic differential curve is calculated. The area ratio S is calculated as the ratio of the area S1 to the area S2.
2. The modified polytetrafluoroethylene according to claim 1, wherein The other monomer is a fluoroalkylethylene.
3. The modified polytetrafluoroethylene according to claim 1, wherein The other monomer is CH2=CH(CF2)4F.
4. The modified polytetrafluoroethylene according to claim 1, wherein The standard specific gravity of the modified polytetrafluoroethylene is 2.130-2.
160.
5. The modified polytetrafluoroethylene according to claim 1, wherein The content ratio of the units based on the other monomers in the modified polytetrafluoroethylene is 1000 to 6000 ppm by mass relative to the content of the units based on all monomers in the modified polytetrafluoroethylene.
6. The modified polytetrafluoroethylene according to claim 3, wherein The content ratio of the units based on CH2=CH(CF2)4F in the modified polytetrafluoroethylene is 1500 to 6000 mass ppm relative to the content of the units based on all monomers in the modified polytetrafluoroethylene.
7. The modified polytetrafluoroethylene according to claim 1, which is used for paste extrusion molding.
8. A molded product obtained by extrusion molding the modified polytetrafluoroethylene paste according to any one of claims 1 to 7. 9 . A method for producing a stretched porous body, comprising extruding the modified polytetrafluoroethylene paste according to claim 1 to obtain extruded beads, and stretching the extruded beads to obtain a stretched porous body.
Citation Information
Patent Citations
Steering device
JP2022114814A
Aqueous emulsion of modified polytetrafluoroethylene, fine powder and method for producing stretched porous body
WO2017030094A1